CLINICAL MANAGEMENT OF URINARY INCONTINENCE IN WOMEN BY FAMILY HEALTH STRATEGY NURSES (Estima – Brazilian Journal of Enterostomal Therapy, 2023)
Objective: To analyze the performance of nurses from the Family Health Strategy (ESF) in the clinical management of urinary incontinence in women in a planning area in the city of Rio de Janeiro (RJ), Brazil. Method: Descriptive research, with a quantitative approach, was carried out in seven Basic Health Units, in the city of Rio de Janeiro. The sample consisted of 27 nurses who worked in the ESF. Data analysis was performed using simple descriptive statistics, with a description of relative and absolute frequency. Results: Weaknesses were shown in the identification of aspects involving an early approach, risk factors for its development, treatment, and educational activities. Conclusion: Despite recognizing that the ESF has the resources for the treatment of uncomplicated urinary incontinence, some actions are not carried out by the nurses, such as involving the team in the care of women with this condition, prescribing exercises to strengthen the pelvic floor and evaluating and carry out non-pharmacologicaltreatment, as well as the investigation of women without complaints of urinary loss. Therefore, the results indicate the urgent need for training of nurses who work in the ESF.